D-A-D fluorogenic probe for the rapid imaging of amyloid β plaques in vivo. (January 2017) - Yang, Hao-Yu; Zhang, Jing-Jing; Zang, Yi; Zhang, Hai-Yan; Li, Jia; Chen, Guo-Rong; He, Xiao-Peng
Abstract: The effective imaging of amyloid β (Aβ) in vivo is important for the diagnosis of Aβ-related diseases such as the Alzheimer's disease (AD). Here we report a donor-acceptor-donor (D-A-D) type fluorogenic probe for the rapid imaging of amyloid β (Aβ) senile plaques in a transgenic mouse brain. The probe that features a dicyanomethylene-4 H -pyran (DCM) core shows a concentration-dependent fluorescence enhancement with Aβ42 and Aβ40, which are the main components of Aβ fibrils formed in the brain of AD patients. The D-A-D probe can also be used to rapidly sense Aβ peptide monomer, oligomer and fibril in an aqueous solution and image the morphologically diverse Aβ species by confocal microscopy. In particular, we demonstrate that the probe can be used to rapidly stain Aβ senile plaques in the brain of transgenic mice by intravenous injection. Graphical abstract: Highlights: Donor-Acceptor-Donor (D-A-D) DCM dye as a new probe for amyloid β (Aβ). The fluorogenic probe rapidly senses Aβ in aqueous solution. The probe can image Aβ of different morphologies. The probe quickly detects the senile plaques deposited in a transgenic mouse brain.